Injury Risk Management in Amateur Badminton Athletes in the Grati Community, Pasuruan Regency: Coach and Athlete Perspectives in Sports Education - Kelvin Ferdiantono , Akhmad; Januardi Irawan, Roy; Rusdiawan, Afif; Nur Bawono, Mokhamad (IJORER : International Journal of Recent Educational Research, 2025)
This study aims to analyze injury risk management practices among amateur badminton athletes by exploring the perspectives of both coaches and athletes in the Grati Badminton Community, Pasuruan Regency. The research seeks to identify key factors influencing injury prevention, response, and recovery processes within community-level sports education. The study incorporates insights from a small circle of individuals who are actively engaged in the community’s training routine, providing a focused and in-depth view of how injury risks are recognized and handled. Data were collected using observation, semi-structured interviews, and documentation techniques, then analyzed through thematic analysis to capture in-depth insights regarding knowledge, attitudes, and practices related to injury risk management. Findings indicate that injury risk management in the community remains largely reactive, with preventive strategies yet to be systematically implemented. Coaches tend to rely on personal experience rather than evidence-based guidelines, while athletes exhibit limited awareness of injury prevention and rehabilitation principles. The absence of standardized operating procedures (SOPs), inadequate medical support, and minimal educational interventions further exacerbate the problem. This study provides a valuable empirical perspective on how grassroots-level badminton communities in rural Indonesia manage injury risks. It highlights the importance of structured educational programs and collaborative efforts between coaches, athletes, and supporting institutions to create safer and more sustainable training environments for amateur athletes.